Pulmonary paracoccidioidomycosis in immunized mice - Faveri, Julio de [UNESP]; Rezkallah -Iwasso, M. T. [UNESP]; Franco, M. F. (My University, 1992)
Paracoccidioidomycosis was induced in immunized (IM) and non-immunized (NI) mice. The histopathology, the number of fungi in the lungs, the cellular (footpad test - FPT and macrophage inhibition factor assay - MIF) and humoral (immunodiffusion test) immune response were investigated serially postinfection. In the IM mice, at days 1 and 3, there was intense and predominant macrophagic-lymphocytic alveolitis with loose granulomatous reaction; at day 30, inflammation was mild. In the NI group, up to day 3, the lesions were focal; later there was formation of extensive epithelioid granuloma. The number of fungi in IM mice were always smaller than those of NI group. Immunization alone induced positive FPT and MIF indices with low titer of antibody. After infection, there was a significant decrease of the FPT indices in the IM group, which we interpreted as desensitization due to trapping of sensitized lymphocytes in the lungs. In conclusion, (1) The lesional pattern of pulmonary paracoccidioidomycosis in IM mice was similar to that of a hypersensitivity pneumonitis. This reaction was probably effective in reducing the extension of the infection and decrease the number of fungi. (2) In this model, pulmonary resistance against P. brasiliensis seems to be related to local and systemic delayed-type hypersensitivity reaction. © 1992 Kluwer Academic Publishers.
Keywords: immunization; Paracoccidioidomycosis; fungus antigen; animal; bacterial count; cellular immunity; immunodiffusion; immunology; leukocyte migration inhibition test; lung mycosis; male; microbiology; mouse; Paracoccidioides; pathology; South American blastomycosis; Animal; Antigens, Fungal; Cell Migration Inhibition; Colony Count, Microbial; Immunity, Cellular; Immunodiffusion; Lung Diseases, Fungal; Male; Mice; Support, Non-U.S. Gov't